2020
DOI: 10.1186/s12992-020-00556-5
|View full text |Cite
|
Sign up to set email alerts
|

A community–based system dynamics approach for understanding factors affecting mental Health and Health seeking behaviors in Beirut and Beqaa regions of Lebanon

Abstract: Background: Available evidence on mental health and psychosocial problems in Lebanon is limited. Recent quantitative data suggests a high prevalence among Syrian refugees and their Lebanese host communities, with significant treatment gaps in both populations. This study aims to determine how Lebanese host and Syrian refugee communities perceive mental health, and identify health seeking behaviors and barriers to health access in two contrasting contexts of fragility. Methods: A comparative qualitative study d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 23 publications
(34 reference statements)
1
38
0
Order By: Relevance
“…Although some of the same justi cations that have been previously cited in the literature may still be used to explain these gender-based variations, other explanations that are speci c to Syrian refugees in Lebanon should be considered. For example, women in refugee settings tend to be subjected to early and forced marriage and bear family responsibilities at an early age, in addition to being exposed to sexual harassment and violence in the household and community at large (Noubani et al, 2020), all of which are potential stressors that increase the risk of developing MDD. Also, these women allude to child rearing and associated responsibilities as important sources of stress and anxiety, especially when considering their worries about the discrimination and bullying their children may face in schools in Lebanon (Noubani et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although some of the same justi cations that have been previously cited in the literature may still be used to explain these gender-based variations, other explanations that are speci c to Syrian refugees in Lebanon should be considered. For example, women in refugee settings tend to be subjected to early and forced marriage and bear family responsibilities at an early age, in addition to being exposed to sexual harassment and violence in the household and community at large (Noubani et al, 2020), all of which are potential stressors that increase the risk of developing MDD. Also, these women allude to child rearing and associated responsibilities as important sources of stress and anxiety, especially when considering their worries about the discrimination and bullying their children may face in schools in Lebanon (Noubani et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For example, women in refugee settings tend to be subjected to early and forced marriage and bear family responsibilities at an early age, in addition to being exposed to sexual harassment and violence in the household and community at large (Noubani et al, 2020), all of which are potential stressors that increase the risk of developing MDD. Also, these women allude to child rearing and associated responsibilities as important sources of stress and anxiety, especially when considering their worries about the discrimination and bullying their children may face in schools in Lebanon (Noubani et al, 2020). Additionally, upon further scrutiny, and although the severity of depression symptoms was comparable among both genders, our ndings indicate that women were signi cantly more likely to report feeling down, having lower energy, and having more suicidal thoughts compared to men, which is consistent with previous ndings (Kim et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is part of a larger project which aimed to examine the dynamics of mental health and psychosocial support from the perspective of both health care professionals and Syrian refugee and Lebanese host community members in Beirut and Beqaa, Lebanon. A detailed account of the methods, including analogous workshops and interviews with community members, and findings of said study can be found in Noubani et al [ 10 ]. We comment on the triangulation of findings against those of this latter study throughout the presentation of results.…”
Section: Methodsmentioning
confidence: 99%
“…This treatment gap may be due to several factors. Recent studies focused on the help- and health-seeking behaviours of individuals suffering from mental and psychosocial issues highlighted that utilization of health services is shaped by high social stigma and treatment costs, limited trust in public health systems and concerns over compromised confidentiality [ 10 – 12 ].…”
Section: Introductionmentioning
confidence: 99%